Sustainable energy technologies for emerging renewable energy and electric vehicles - Surender Reddy Salkuti (AIMS Energy)
Renewable energy and electric vehicles are used globally for reducing fuel dependency and carbon footprints. Here, I explore the complex field of 'Sustainable Energy Technologies for Emerging Renewable Energy and Electric Vehicles' and examined the most recent advancements, obstacles, and ideas that are promoting the effective use of renewable energy sources (RESs), energy storage systems (ESSs), and electric vehicles (EVs). I focused on the integration of renewable energy (RE), energy storage (ES), and EVs into modern sustainable power grids. With the recent advances in power generation technologies, the fluctuations in generation and electrical demand are common in hybrid power systems. This special issue was aimed at addressing the economic challenge of integrating RESs, ES, and EVs to improve the resilience and flexibility of grid operations. The widespread adoption of intermittent RESs and EVs makes it difficult to maintain a consistent power supply and significantly impacts grid stability. To address this challenge, ESSs are emerging as a potential solution. With the right investments and policies in place, RE, ES, and EVs can play a significant role in creating a more sustainable energy landscape worldwide.